Standardization of original medicine anti-alcohol action on assay of glycin - Rudakova, Olha; Gubar, Svitlana; Kriukova, Anna; Smielova, Nataliia; Bezchasnyuk, Elena (ScienceRise: Pharmaceutical Science, 2019)
Aim. Development and validation of an accessible method for the quantitative determination of glycine in a new original drug used in condition of alcohol dependence. Methods. To quantify glycine in a drug in the form of an effervescent powder for the preparation of an oral solution, a spectrophotometric method was developed and validated using a Specord 200 spectrophotometer from “Analytik Jena”. Results. As a result of the study, a modified sensitive method for the quantitative determination of glycine by a spectrophotometric method was developed. The optimal conditions for carrying out the glycine – ninhydrin reaction were selected in order to obtain stable analysis results: analytical wavelength – 568 nm; heating the reaction mixture is carried out in a boiling water bath for 30 minutes; the volume of the buffer solution is 4 ml, the pH of the buffer solution is 6.8, and a reducing agent – ascorbic acid was introduced. It was established that the methodology does not have a systematic error; the relative uncertainty for the probability of 95 % does not exceed the maximum allowable uncertainty of the analysis results (1,77 % ≤ 2,4 %). Validation parameters such as specificity, linearity, accuracy, precision and robustness were studied for the glycine quantification procedure. It was established that all calculated validation parameters meet the acceptability criteria. Conclusions. An accessible sensitive spectrophotometric technique based on the ability of the products of the interaction of glycine with ninhydrin to absorb in the visible region of the spectrum has been developed and validated. All validation parameters meet the acceptability criteria